Ionic‐liquid‐based ultrasound/microwave‐assisted extraction of 2, 4‐dihydroxy‐7‐methoxy‐1, 4‐benzoxazin‐3‐one and 6‐methoxy‐benzoxazolin‐2‐one from maize (Zea mays L.) seedlings. Issue 2 (11th December 2014) - Li, Chunying; Lu, Zhicheng; Zhao, Chunjian; Yang, Lei; Fu, Yujie; Shi, Kunming; He, Xin; Li, Zhao; Zu, Yuangang
<x xml:space="preserve">Abstract</x> We evaluated an ionic‐liquid‐based ultrasound/microwave‐assisted extraction method for the extraction of 2, 4‐dihydroxy‐7‐methoxy‐1, 4‐benzoxazin‐3‐one and 6‐methoxy‐benzoxazolin‐2‐one from etiolated maize seedlings. We performed single‐factor and central composite rotatable design experiments to optimize the most important parameters influencing this technique. The best results were obtained using 1.00 M 1‐octyl‐3‐methylimidazolium bromide as the extraction solvent, a 50°C extraction temperature, a 20:1 liquid/solid ratio (mL/g), a 21 min treatment time, 590 W microwave power, and 50 W fixed ultrasonic power. We performed a comparison between ionic‐liquid‐based ultrasound/microwave‐assisted extraction and conventional homogenized extraction. Extraction yields of 2, 4‐dihydroxy‐7‐methoxy‐1, 4‐benzoxazin‐3‐one and 6‐methoxy‐benzoxazolin‐2‐one by the ionic‐liquid‐based ultrasound/microwave‐assisted extraction method were 1.392 ± 0.051 and 0.205 ± 0.008 mg/g, respectively, which were correspondingly 1.46‐ and 1.32‐fold higher than those obtained by conventional homogenized extraction. All the results show that the ionic‐liquid‐based ultrasound/microwave‐assisted extraction method is therefore an efficient and credible method for the extraction of 2, 4‐dihydroxy‐7‐methoxy‐1, 4‐benzoxazin‐3‐one and 6‐methoxy‐benzoxazolin‐2‐one from maize seedlings.